Implementasi Teknik Audio Pada Pembuatan Film Pendek “Demi Cinta” - Marcella Aprilia Bandua; Anton Topadang; Agusdi Syafrizal (CV MEDAN TEKNO SOLUSI, 2024)
Sound is an important element in enhancing the visuals in a movie and providing a deep emotional dimension to the audience's experience. With proper use, sound can be an effective tool in creating strong emotional engagement and bringing the overall atmosphere of the movie to life. The main process of making a short film is to consider the selection of appropriate audio to achieve a deep dramatic impression. Adobe Premiere Pro as an application used to edit video and audio. This research produces a short film that implements audio settings with the title “Demi Cinta” which lasts 16 minutes 24 seconds, and is published through the youtube page with the URL https://youtu.be/JDHMKfO7MyQ?si=fmvmTj4je8BcHGyK, with 322 views, 69 likes, 31 comments, 358 subscribers.